S95 SOCCAR: Internationally Resonant Results from a Randomised Trial Based on UK Clinical Practise. (19th November 2012) - Maguire, J; O'Rourke, N; McNememin, R; Peedell, C; Snee, M; Kelly, V; Khan, I
Abstract : Concurrent chemoradiation is now recognised as a standard of care for patients with inoperable Stage III NSCLC and good Performance Status. Two year survival rates in published trials ranges from 29% to 43%, with median survival in the range of 14 to 17 months. An ongoing multi-centre study performed in the United States has recently reported median survival of 21 months for this group of patients, with no advantage from dose escalation from 60 to 74 Gy in conventional fractionation. In SOCCAR, we employed a standard UK radical lung cancer radiotherapy treatment schedule; 130 patients were randomised to receive 55Gy in 20 fractions over 4 weeks, given either concurrently or sequentially with cisplatinum and vinorelbine. Trial entry criteria were: pathologically confirmed stage III NSCLC, judged in-operable by a thoracic surgeon and treatable within a radical radiotherapy volume with V20 <30% and <12 cm oesophagus in PTV. Patients were required to have PS 0 or 1, FEV1 >/= 1L and TLCO >/= to 50%. Patients with weight loss and N3 disease were included, with no upper age limit. Characteristics were well balanced between the two arms. Results: Median survival is 27.4 months in the concurrent arm and 18.6 months in the sequential arm. Two year survival rates are 54% and 42% respectively. Toxicity was acceptable and similar in both arms. Documented local relapse was 10% in the concurrent arm and 22% in the sequential arm. Quality of Life was measured prospectivly in all patients, there being no significant difference in either arm. In comparison with 16 published RCTs, comprising 1733 patients treated with concurrent chemoradiation, the concurrent treatment arm in SOCCAR ranks top in survival with comparable toxicity. These results are recognised as being of major relevance internationally and are the basis of a proposed multi-centre international study.